Animals, divorce and legal consequences - Camilo Henrique Silva (INTERthesis, 2015)
This work, through bibliographic research of laws, judicial decisions and doctrine, intends to present to the reader, in an objective manner, the reflections and the position of the Brazilian legislation on the issue of domestic animals involved in disputes custody in divorce proceedings. In this context, this paper addresses the Brazilian legislation regarding custody, visitation rights and alimentation, and its use, by analogy, in the case of pets, due to the absence of a specific rule. We describe how the judges and courts are positioned in the cases prosecuted and present the requirements to be followed to decide the dispute, with a view to the welfare and interest of the animal. In proceedings involving pets, it becomes legal to give the custody and visitation rights to spouses/guardians and establish an obligation to provide food to animals.